Predicted maximal heart rate for upper body exercise testing. (16th October 2014) - Hill, M.; Talbot, C.; Price, M.
Summary: Age‐predicted maximal heart rate (HRMAX ) equations are commonly used for the purpose of prescribing exercise regimens, as criteria for achieving maximal exertion and for diagnostic exercise testing. Despite the growing popularity of upper body exercise in both healthy and clinical settings, no recommendations are available for exercise modes using the smaller upper body muscle mass. The purpose of this study was to determine how well commonly used age‐adjusted prediction equations for HRMAX estimate actual HRMAX for upper body exercise in healthy young and older adults. A total of 30 young (age: 20 ± 2 years, height: 171·9 ± 32·8 cm, mass: 77·7 ± 12·6 kg) and 20 elderly adults (age: 66 ± 6 years, height: 162 ± 8·1 cm, mass: 65·3 ± 12·3 kg) undertook maximal incremental exercise tests on a conventional arm crank ergometer. Age‐adjusted maximal heart rate was calculated using prediction equations based on leg exercise and compared with measured HRMAX data for the arms. Maximal HR for arm exercise was significantly overpredicted compared with age‐adjusted prediction equations in both young and older adults. Subtracting 10–20 beats min −1 from conventional prediction equations provides a reasonable estimate of HRMAX for upper body exercise in healthy older and younger adults.